Manejo integrado de cochonilhas (Pseudococcidae) em videira no submédio do Cale do São Francisco - Souza, Geisa Mayana Miranda de (2016)
Several insect pests attack the grape culture in the submedium San Francisco Valley example of mealybugs of Pseudococcidae Family. The aim of this study was to find strategies, based on chemical control and from natural products, for the management of mealybugs Planococcus citri (Risso), Phenacoccus solenopsis (Tinsley) and Maconellicoccus hirsutus (Green), as well as to assess the compatibility of these products the predator C. montrouzieri. Commercial insecticides were tested Epingle® in association with Sumirody® and mineral oil (Agris Union Agro®) for different doses of Epingle®; and Epingle® associated only with mineral oil, furthermore verified the efficiency of the mineral oil alone. Insecticides cited were tested via spraying under field conditions in the laboratory and on the pink hibiscus mealybug (M. hirsutus). It was also observed selectivity of these products at different stages of development C. montrouzieri. By applying the soil was evaluated the efficiency of two registered neonicotinoids (Actara® and Nuprid®) and one in registration phase (NUF220F2) also aimed at controlling of M. hirsutus. For the management P. citri and P. solenopsis used two commercial natural products: orange oil-based (Orobor®) and extracts of seaweed (Matrix®), applied two or three times on individuals in adulthood. As a result, mixtures containing pyriproxyfen (Epingle®) + fenpropathrin (Sumirody®) + mineral oil (Agris Union Agro®), regardless of the dose used, demonstrated efficiency above 80% against M. hirsutus, both in the field and in the laboratory, however, they proved to be harmful to all developmental stages of C. montrouzieri. The mineral oils generally showed low efficiency in controlling on the pink hibiscus mealybug, however, was selective most predator development stages studied. The neonicotinoids thiamethoxam the base (Actara® and NUF220F2) were more effective in controlling pink hibiscus mealybug in relation to imidacloprid (Nuprid®). With three applications products orange oil and seaweed cause significant mortality P. solenopsis and P. citri. Com two applications, only the product based on seaweed caused high mortality in Ph. solenopsis. There was a high survival rate of C. montrouzieri adults subjected to two exposures of the product based on seaweed. The orange oil was not selective to adult C. montrouzieri.